Tiny room at Bob Bungalow with cats - Mumbai Archive Project Team (Jio Institute, 2024)
Shenaaz's tiny room at Bob Bungalow is where she feeds the local cats. Many cats live in Mazagon, where they patrol the fish markets and serve as useful pest deterrents. The residents look after the cats even if they are not domesticated. They become close friends with the locals and are regarded as family.